Rekontruksi Penyusunan Laporan Keuangan pada BUMDes berdasarkan SAK ETAP - Amanda Esa Pangesti; Yulinartati Yulinartati; Astrid Maharani (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the preparation of the financial statements of the BUMDes Pesat Oyster Mushroom Business Unit in 2020 in Pontang Village based on SAK ETAP. The method in this research is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results showed, based on SAK ETAP, there should be 5 (five) financial statements, namely balance sheet, income statement, statement of changes in equity, cash flow statement and notes to financial statements. However, the financial report by BUMDes Pesat Oyster Mushroom Business Unit presents financial reports in the form of income and expenses. In conclusion, the BUMDes Oyster Mushroom Business Unit has not presented financial reports based on SAK ETAP. Keywords: BUMDes, Financial Statements, SAK ETAP